Affordances and Constraints for Equity-Minded School Mental Health Policy Change: A District Case Study Centering the Perspectives of Community-Based Mental Health Service Providers - Kate Somerville (American Educational Research Journal, 2026)
Schools are central settings for youth mental health support, yet less research has examined policy environments shaping what is possible in school-based mental health systems. This study examines the zone of mediation for equity-minded school mental health policy change in one urban district, centering perspectives of six community-based mental health providers occupying peripheral positions between school and community organizations. Findings reveal that intersecting technical, normative, and political factors—including workforce shortages, deficit-based beliefs among potential providers, and the overburdening of schools as the primary site for addressing community-level need—produce systemic conditions that constrain the potential for equity-minded change. These findings carry implications for principal preparation, intervention design, and health, education, and social policy.